Coming out of the Shadows: Learning about Legal Status and Wages from the Legalized Population - Kossoudji, Sherrie A.; Cobb‐Clark, Deborah A. (Journal of Labor Economics, 2002)
The 1986 Immigration Reform and Control Act (IRCA) granted amnesty to approximately 1.7 million long‐term unauthorized workers in an effort to bring them “out of the shadows” and improve their labor market opportunities. An analysis of wages using panel data for a sample of legalized men provides evidence that wage determinants are structurally different after amnesty for them but not for the comparison group as measured during the same time periods. The wage penalty for being unauthorized is estimated to range from 14% to 24%. The wage benefit of legalization under IRCA was approximately 6%.